Direct growth of triple cation metallorganic framework on a metal substrate for electrochemical energy storage - Rajan, Jose; M. K., M. Zain; Bincy Lathakumari, Vijayan; I., I. Misnon (2018)
Metal-organic frameworks (MOFs) received tremendous attention in recent years as emerging materials for electrochemical energy storage applications. The robust frameworks with high surface area together with open metal center sites which easily undergo the reversible redox reaction without damaging the initial framework are the bonus points for MOFs as an electrode for electrochemical energy storage. Furthermore, MOFs provide a practical solution where rare, precious, and high performing metals are to be exploited for their full potential.